2022
DOI: 10.1088/1755-1315/967/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of functional bioactive peptides derived from fish protein hydrolysate

Abstract: By-product removal in fish processing is estimated to be between 25 and 70% due to improper fish production handling and significant problems in the fish industry today. Therefore, one of the ways to manage the raw material of by-product is through protein hydrolysis. However, one of the most effective methods for managing this raw material, which includes skin, bones, heads, and viscera, is to convert their protein into peptides via hydrolysis methods, resulting in fish protein hydrolysate (FPH). FPH has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…To fix the situation, effective methods are needed to transform fish by-product wastes into important nutrients. A large percentage of by-products account for 50% to 70% of the original raw material, which contains collagen-rich heads, viscera, skin, bone, scales, and fins, depending on the processing method [ 9 , 10 ]. Moreover, fish skin has a high protein content, and collagens generated from fish skin have a wide range of applications as functional food components [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fix the situation, effective methods are needed to transform fish by-product wastes into important nutrients. A large percentage of by-products account for 50% to 70% of the original raw material, which contains collagen-rich heads, viscera, skin, bone, scales, and fins, depending on the processing method [ 9 , 10 ]. Moreover, fish skin has a high protein content, and collagens generated from fish skin have a wide range of applications as functional food components [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fish skin has a high protein content, and collagens generated from fish skin have a wide range of applications as functional food components [ 2 ]. Furthermore, fish by-products also include a high amount of crude protein, ranging from 8 to 35%, and can be used as a source of collagen, gelatin, polyunsaturated fatty acids, enzymes, and essential amino acids [ 10 ]. Fish collagen has been used in the development of protein nutritional multivitamins, transporters, food additives, edible films, and coatings [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of survival of S. enterica at higher FPH concentrations can be attributed to an increase in the concentration of bioactive peptides, leading to an inhibitory effect on the test microorganisms. 39,40 A pattern similar to that of CH and SPH was observed with FPH being unable to impart cryoprotection to S. enterica at -18±3°C with no growth observed from Day 7 onwards.…”
Section: Effects Of Fph On the Survival Of S Entericamentioning
confidence: 62%
“…Several studies have reported the potential of bioactive peptides from fermented fish as antibacterial and anti-cholesterol agents in addition to their activity as an antioxidant and ACE inhibitor (Kusmarwati et al, 2014;Rinto et al, 2019). The FPIMGHGSRPA peptide sequences with 12 amino acids have been shown to have antibacterial action against Gram-positive and Gram-negative bacteria (Baco et al, 2022).…”
Section: Peptide Bioactive and Peptide Bioactivity In Rusipmentioning
confidence: 99%